Milko Matičetov e i paesi slavi del Molisi - Cirese, Alberto Mario (Traditiones (Ljubljana), 1999)
In his article the author remembers the beginnings of scientific cooperation and almost five decades of friendship with Milko Matičetov. He writes about two articles whic have not been published yet. Together with the author and the author's father Eugenio Milko Matičetov contributed important knowledge about Slavic villages in Molise, an area in Italy
Keywords: Matičetov, Milko, 1919-; ethnology; etnologija; Slavs; Slovani; Italija; Italy